Ball Fishing Game Activity as a Medium for Mild Dementia Therapy in the Eld - Herni Sulastien; Siti Zuraida Muhsinin; Baiq Amalia Sholiha; Baiq Susanti (Indonesian Journal of Global Health Research, 2024)
The elderly represents the final stage in the human life process, characterized by various physical, cognitive, and functional limitations that arise due to the degenerative process. According to statistical data from 2022, the proportion of the elderly population increased from 7.57% in 2021 to 10.48% in 2022. One of the most prevalent conditions among the elderly is dementia, which manifests as a progressive decline in memory, cognitive abilities, and the capacity to perform daily activities. Without intervention, dementia symptoms worsen over time, necessitating targeted therapeutic approaches to prevent its progression. Engaging in recreational activities, such as playing games, has been shown to keep the mind active and foster cognitive engagement. This is particularly important for the elderly, especially those at risk of or experiencing mild dementia. The "Ball Fishing Game" is a simple yet engaging activity that involves the use of locally crafted wooden tools, woven bowls, and plastic balls. This game aims to stimulate cognitive functions, enhance memory, and improve concentration in 11 elderly individuals. The objective of this study was to evaluate the effectiveness of the Ball Fishing Game as a therapeutic medium for managing mild dementia in the elderly. A quasi-experimental research design was used, utilizing a one-group pretest-posttest approach to assess the effect (impact) of the intervention. Statistical analysis using a correlation test yielded a significance (sig.) value of 0.021 (<0.05), indicating a significant effect of the Ball Fishing Game on reducing Mini-Mental State Examination (MMSE) scores in elderly individuals with mild dementia. Furthermore, a paired sample t-test yielded a sig. (2-tailed) value of 0.005 (<0.05), indicating a significant difference between pretest and posttest MMSE scores following the intervention. In conclusion, the Ball Fishing Game is an effective therapeutic medium for managing mild dementia in elderly individuals.